Electronic Democracy in Europe Prospects and Challenges of E-Publics, E-Participation and E-Voting - Lindner, Ralf.; Aichholzer, Georg; Hennen, Leonhard; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This edited book is the first of its kind to systematically address the intersection of e-democracy and European politics. It contributes to an improved understanding of the role that new media technologies play in European politics and the potential impact that Internet-based political participation processes may have on modern-day representative democracy in Europe. A unique, holistic approach is taken to examine e-democracy's current state and prospects in Europe from three, partially overlapping and interlocking perspectives: e-public, e-participation and e-voting. The authors provide both theory-inspired reflections on e-democracy's contribution to the formation of the European public sphere, as well as rich empirical analyses of contemporary e-participation phenomena such as the European Citizens' Initiative or e-voting practices in Estonia. Based on the presented findings, the concluding chapter combines a prospective outlook with recommendations for future paths towards meaningful integration of e-democracy in European politics and governance.
Acknowledgements -- Electronic Democracy in Europe. An Introduction -- Part I: The E-Public in Europe -- Part II: E-Participation -- Part III: E-Voting.
Keywords: Democracy; European Economic Community lite; Economic policy